Burden and factors influencing intestinal parasitic infections among food handlers in Gondar City, Northwest Ethiopia - Getie, Michael; Belay, Gizeaddis; Amare, Azanaw; Abebe, Wondwossen; Deress, Teshiwal (Frontiers in Public Health, 2024)
Intestinal parasitic infections pose significant global health challenges, particularly in developing countries. Asymptomatic infections often present a considerable burden with food handlers serving as potential carriers. In Ethiopia, the prevalence of these parasites varies across regions, and accurate data in the study area is lacking. Therefore, this study aimed to investigate the prevalence of intestinal parasites among food handlers working in hotels and restaurants in Gondar City, Northwest Ethiopia. A cross-sectional study collected stool samples from food handlers alongside a structured questionnaire gathering socio-demographic and hygiene practice information. Stool specimens were screened for intestinal parasites using direct wet mount and formol-ether concentration techniques. The collected data were checked for completeness, entered into EpiData software version 3.1, and exported to SPSS version 20 for analysis. A multivariable logistic regression analysis was deemed statistically significant if the p-value was less than 0.05. A total of 257 food handlers working in hotels and restaurants in Gondar City participated in the study. Of these, 33.5% (86/257) were found positive for one or more intestinal parasites, with a 95% confidence interval (CI) of 28.0 -39.5%. The study identified nine types of intestinal parasites, with E. histolytica/dispar (8.2%, 21/257) and Ascaris lumbricoides (6.6%, 17/257) being the predominant parasites, followed by hookworm (3.5%, 9/257) and S. mansoni (2.3%, 6/257). The prevalence of mixed infections was 9.3% (24/257). A significant association was observed between intestinal parasitic infection and the educational level of food handlers. In this study, a high prevalence of intestinal parasites was detected indicating poor hygiene practices of the food handlers at the study site. Even the prevalence of mixed infections was high. Regular training, strict adherence to personal hygiene and food-handling practices, and routine inspections and medical checkups for food handlers are crucial.